PEER TUTOR METHOD INTEGRATED WITH SHORT CARD MEDIA: ITS IMPLEMENTATION IN ARABIC LANGUAGE LEARNING - Taufiq, Ahmad; Annur, Aan Fadia; Rif’iyati, Dian; Hasanah, Fatmawati Nur (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
Arabic is a subject that has its difficulties for students of Islamic Primary Schools. The majority of students at Madrasah Ibtidaiyah struggle with reading, writing, and understanding mufradat (vocabularies) in Arabic classes. Among the attempts undertaken to overcome these obstacles is the application of the peer tutoring method combined with short card media in Arabic language learning. This study aimed to determine and analyze the implementation of the peer tutor method integrated with short card media in learning Arabic at Madrasah Ibtidaiyah. The subjects in this study were teachers and students in learning Arabic at Madrasah Ibtidaiyah. The method used qualitative-descriptive. The results showed that the peer tutoring method integrated with short card media was carried out through the following stages: 1) explanation of the objectives and classical learning activities by the teacher, 2) grouping students into teams where some of the students functioned as tutors for the others, 3) learning with the peer tutor method integrated with short cards media that have been provided, 4) observing learning activities, and 5) evaluating learning activities with teachers and students. When employing peer tutoring integrated with short card media, the findings indicate that students showed a higher level of enthusiasm for their participation in the learning process.